2020
DOI: 10.1021/acssuschemeng.0c04647
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Amination of Biobased Levulinic Acid to Unnatural Chiral γ-Amino Acid Using an Engineered Amine Dehydrogenase

Abstract: Optically pure (S)-4-aminopentanoic acid is a pivotal precursor in the synthesis of therapeutic molecules and pyrrolidinone derivatives. Enantioselective reductive amination of levulinic acid catalyzed by amine dehydrogenases, a readily sustainable material from biobased lignocellulosic waste, represents an attractive approach for the synthesis of (S)-4-aminopentanoic acid. However, the natural amine dehydrogenases reported so far showed insufficient activity toward levulinic acid. Herein, we engineered a natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 59 publications
0
27
0
Order By: Relevance
“…With the column temperature maintained at 30°C, mobile phase H 2 SO 4 (5 mM) ran at a flow rate of 0.6 ml/min. ( Cai et al, 2020 ). ( R )-4-aminopentanoic acid in the reaction mixtures were labeled using 1-fluoro-2,4-dinitrophenyl-5-L-alanineamide (FDAA) and then analyzed on a Develosil ODS-UG-5 column (150 × 4.6 mm).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the column temperature maintained at 30°C, mobile phase H 2 SO 4 (5 mM) ran at a flow rate of 0.6 ml/min. ( Cai et al, 2020 ). ( R )-4-aminopentanoic acid in the reaction mixtures were labeled using 1-fluoro-2,4-dinitrophenyl-5-L-alanineamide (FDAA) and then analyzed on a Develosil ODS-UG-5 column (150 × 4.6 mm).…”
Section: Methodsmentioning
confidence: 99%
“… Mayol et al (2016) identified a wild-type amine dehydrogenase from Petrotoga mobilis ( Pm AmDH), which is capable of reductive amination of LA to ( S )-4-aminopentanoic acid. Subsequently, Cai et al (2020) engineered Pm AmDH through directed evolution and obtained mutants with increased activity, thereby achieving efficient synthesis of ( S )-4-aminopentanoic acid. However, there are still no relevant reports on the dehydrogenase that converts LA into ( R )-4-aminopentanoic acid.…”
Section: Introductionmentioning
confidence: 99%
“…20,23 Even naturally occurring amine dehydrogenases have been engineered to improve their substrate specicity and catalytic efficiency. Cai et al 24 have synthesized g-aminobutyric acid from biobased lignocellulosic waste using an engineered amine dehydrogenase.…”
Section: Synthesis Of Uaasmentioning
confidence: 99%
“…A new generation of chemical and drug discovery tools has emerged from conformationally constrained peptides. Asymmetric alkylation of a uorine-modied Ni(II) Schiff base complex (23,24) yielded an unnatural alkenyl amino acid (25,26) required for peptide 'stapling' (Fig. 2c).…”
Section: Chemical Synthesismentioning
confidence: 99%
“…Chiral amines are important components of many significant bioactive compounds, pharmaceutical intermediates and agrochemical industry products (Bornscheuer et al, 2012 ; Mathew and Yun, 2012a ; Ghislieri and Turner, 2014 ; Park et al, 2014 ; Fuchs et al, 2015 ; Ferrandi and Monti, 2017 ; Dawood et al, 2018 ; Cai et al, 2020 ). In addition to optical rotation, enantiomers of chiral drugs have the same physical properties, but they are absorbed, activated or degraded by the metabolic system of the human body in different ways during the pharmacological action, resulting in different efficacies and toxicities (Burke and Henderson, 2002 ).…”
Section: Introductionmentioning
confidence: 99%